De lá para cá ou dos percursos que a diversidade sexual faz na constituição de uma política na UFSCar (2004-2016) - Vieira, Hamilton Édio dos Santos (Universidade Federal de São Carlos, 2019)
This thesis presents the result of an investigation on the field of semantic significance of sexual diversity from institutional documents of the Federal University of São Carlos, through the interactional perspective of language, which takes place in and with social relations. Thus, it tried to observe the processes that constituted the senses of diversity and that crossed the statements constructed later in sexual diversity, having as sources of analysis the documents that the UFSCar produced in the last two decades. In order to show a reading of the course of meanings with which sexual diversity presented, contextualizing education and the role of university institutions when they crossed by discussions that touch on social segments that demand their specificities in the public space. This university chosen following a methodological strategy, when it was perceived that there is a permeated path in the discourses of the documents chosen to be located between 2004, when diversity appears the first time, until 2016, when sexual diversity gains its space, building an administrative organization not found in other federal universities. The hypothesis was that sexual diversity, before its chronological emergence in the UFSCar, took place in the discussion about diversity as a semantic field to think about the development of the university from 2004 on. Using the field of language to perceive the expressive and subjective side of the verbal and non-verbal signs in the production of the senses about sexual diversity was possible from a working method centered on the Indicium Paradigm. This form of investigative work focuses on the detail of the observation and allows searching for clues and evidences with which the researcher has the tools to observe for which paths these clues have walked and how much they indicate about the investigated object and a field of palpable answers presented. By the paradigm, it tried to value the specificity of the field with which the discussion about diversity and sexual diversity emerged, which was possible to conclude that theme sexual diversity cross by the symbolic construction of diversity and how this semantic field articulates the space of diversity in institutional policies. The research seeks to reinforce that language is above all a social production, is not neutral and intended among the singularities of different subjects. Through the register, that existence give, that is, the emergence of sexual diversity allows the materiality of life can be look at and function as an analytical category on how society deals in its public space with the specificities that it produces.
Back and forth or the paths that sexual diversity makes in the construction of Meanings in UFSCar (2004-2016)
Keywords: Produção de sentidos; Diversidade sexual; História da educação; Production of meanings; Sexual diversity; History of education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO